The role of excitons within the hole transporting layer in quantum dot light emitting device degradation. Issue 17 (15th April 2019) - Davidson-Hall, Tyler; Aziz, Hany
Abstract : Electroluminescence and photoluminescence stability of QDLEDs is found to depend on the hole transporting layer and materials that are highly susceptible to exciton-induced degradation can negatively impact QDLED stability. Abstract : This work investigates the root causes of the limited stability of electroluminescent quantum dot light-emitting devices (QDLEDs). Studies using electrical measurements, continuous UV irradiation, and both steady-state and transient photoluminescence (PL) spectroscopy reveal that exciton-induced degradation of the hole transporting material (HTM) in QDLEDs plays a role in limiting their electroluminescence (EL) stability. The results indicate that there is a correlation between device EL stability and the susceptibility of the HTM to exciton-induced degradation. The presence of quenchers in the HTM layer can lead to a decrease in the luminescence quantum yield of QDs, suggesting that energy transfer between the QD and HTM films may play a role in this behavior. The results uncover a new degradation mechanism where excitons within the HTM limit the EL stability of QDLEDs.